In vitro studies evaluating the effects of biofilms on wound‐healing cells: a review. Issue 4 (April 2017) - Kirker, Kelly R.; James, Garth A.
Abstract : Chronic wounds are characterized as wounds that have failed to proceed through the well‐orchestrated healing process and have remained open for months to years. Open wounds are at risk for colonization by opportunistic pathogens. Bacteria that colonize the open wound bed form surface‐attached, multicellular communities called biofilms, and chronic wound biofilms can contain a diverse microbiota. Investigators are just beginning to elucidate the role of biofilms in chronic wound pathogenesis, and have simplified the complex wound environment using in vitro models to obtain a fundamental understanding of the impact of biofilms on wound‐healing cell types. The intent of this review is to describe current in vitro methodologies and their results. Investigations started with one host cell‐type and single species biofilms and demonstrated that biofilms, or their secretions, had deleterious effects on wound‐healing cells. More complex systems involved the use of multiple host cell/tissue types and single species biofilms. Using human skin‐equivalent tissues, investigators demonstrated that a number of different species can grow on the tissue and elicit an inflammatory response from the tissue. A full understanding of how biofilms impact wound‐healing cells and host tissues will have a profound effect on how chronic wounds are treated.